Dynamic simulation model of a parabolic trough collector system with concrete thermal energy storage for process steam generation - Sattler, Johannes Christoph; Alexopoulos, Spiros; Caminos, Ricardo Alexander Chico; Mitchell, John; Ruiz, Victor; Kalogirou, Soteris A.; Ktistis, Panayiotis K.; Boura, Cristiano Teixeira; Herrmann, Ulf (My University, 2019)
Parabolic trough collector (PTC) systems are commercially available concentrating solar power plants widely known for their application to generate electrical power. To further reduce the dependency on fossil fuels, such systems can also be deployed for producing process heat for industrial purposes. In combination with a thermal energy storage system, this technology has the ability to reliably supply on-demand process heat. This paper gives details on a fully automated PTC system with concrete thermal energy storage (C-TES) and kettle-type boiler that supplies saturated steam for a beverage factory in Limassol, Cyprus. In the focus is the validation of a dynamic simulation model in Modelica® that physically describes the entire PTC system. The simulation model uses various plant data as inputs including mirror reflectivity and weather data from on-site measurements. The validation was carried out in three steps. First, the PTC was validated as a stand-alone component. A time-dependent inlet oil temperature vector was given as input and the outlet oil temperature was computed. The root mean square (rms) error between the measured to simulated outlet oil temperature values results in 3.86 % (equivalent to about 1.9 K). The second part of the validation then considered a complete PTC oil cycle in PTC-and-boiler operation mode (without C-TES). In the simulation, both the PTC inlet and outlet oil temperatures were computed. The result is a deviation < 4.25 % (rms) between measured to simulated values. Finally, in the third step, the C-TES model was validated as a stand-alone component. The deviation between measurement and simulated values is < 5 % compared to the design point.
Keywords: Solar energy; Solar collectors; Absorber tube